Acid-promoted bicyclization of arylacetylenes to benzobicyclo[3.2.1]octanes through cationic rearrangements. Issue 24 (3rd March 2016) - Su, Xiang; Sun, Yihua; Yao, Jiannian; Chen, Hui; Chen, Chao
Abstract : Acid-promoted site- and stereo-selective bicyclization of alkynes to benzobicyclo[3.2.1]octanes was realized with atom- and step-economy. The reaction proceeded through two C–C bonds formed on remote alkyl C–H bonds via twice long-distance cationic rearrangement. Abstract : Acid-promoted efficient, site- and stereo-selective bicyclization of alkynes to polycyclic compounds (benzobicyclo[3.2.1]octanes) was realized with atom- and step-economy. The reaction proceeded through two C–C bonds formed on remote alkyl C–H bonds via twice long-distance cationic rearrangement.